Roles of Alkaloids from Medicinal Plants in the Management of Diabetes Mellitus - Bikash Adhikari (Journal of Chemistry)
Medicinal plants play a fundamental part in health sectors via the management of different infectious diseases because of their wide plenitude wellspring of bioactive phytochemicals. Research activities on them have got attention throughout the world in the present days in search of low-cost and safe compounds for the management of diabetes. This is the literature-based analysis of alkaloids from medicinal plants in preventive or treatment approaches to diabetes. The most abundant and diversified group of secondary metabolites, i.e., alkaloids, show antidiabetic activity through the inhibition of enzymes (α-amylase, α-glucosidase, aldose reductase, dipeptidyl peptidase-IV, and protein tyrosine phosphatase-1B); inhibition of advanced glycation end products; increment of insulin secretion and its sensitivity; enhancement of glucose uptake; and their antioxidant ability. The study is useful for the examination of dynamic alkaloids for the advancement of a new medication for mankind.